Distal Femoral Osteotomy: Lateral Opening Wedge Technique - Michael P. O'Malley, M.D.; Ayoosh Pareek, B.S.; Patrick. J. Reardon, B.S.; Michael J. Stuart, M.D.; Aaron J. Krych, M.D. (Arthroscopy Techniques, 2016)
Coronal limb malalignment is a significant contributor to asymmetric joint wear, gait abnormalities, and the development and progression of degenerative joint disease. Osteotomies about the knee were developed to realign the mechanical axis of the limb to unload the affected compartment. Valgus malalignment is less common than varus malalignment, but can contribute to a variety of clinical conditions, including lateral compartment cartilage defects and arthritis, lateral patellofemoral instability, and medial collateral ligament laxity. In this article, we describe our preferred operative technique for a lateral opening wedge varus-producing distal femoral osteotomy to correct mild to moderate valgus malalignment.